Fenomena Misandry di Dunia Maya: Studi Kasus Tentang Kebencian Terhadap Pria di Sosial Media - Hisyam, Ciek Julyati; Islami, Prima Yustitia Nurul; Anas, Diva Kayla Nazwa; F, Faridah; Ginting, Nindia Monita Br; Khoiriah, Siti Umi; Augea, Syafa Marwah; Purba, Vinsensia Carolin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The phenomenon of misandry on social media is increasingly prominent as awareness of gender equality issues increases. Misandry, which is hatred towards men, often appears in the form of memes, comments, and long threads containing negative generalizations towards men. This study aims to examine how misandry speech is produced, disseminated, and interpreted in a digital context, using a qualitative approach based on literature studies. R.W. Connell’s hegemonic masculinity theory is used as the main theoretical framework. The findings show that although mIsandry can be interpreted as a form of resistance to patriarchal domination, this expression often shifts into a new form of symbolic violence that targets all men regardless of their context and identity. Digital space, as a participatory arena, allows women and marginalized groups to voice their experiences, but is also prone to giving rise to destructive counter-discourses if not accompanied by critical awareness. Therefore, it is important to distinguish between criticism of patriarchal structures and gender-based hate speech, so that the discourse of equality does not turn into a reproduction of new forms of inequality.